2014
DOI: 10.3945/ajcn.113.081745
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis examining the effect of eating rate on energy intake and hunger

Abstract: Evidence to date supports the notion that eating rate affects energy intake. Research is needed to identify effective interventions to reduce eating rate that can be adopted in everyday life to help limit excess consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
270
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(291 citation statements)
references
References 38 publications
18
270
1
2
Order By: Relevance
“…While the type and quantity of foods consumed and the associated meal patterns that support sustained positive energy balance are important contributors to early weight gain, limited research has focussed on exploring whether children exhibit patterns of food oral processing, or "eating microstructure" patterns [2], that support increased energy intake within a meal. Previous research has shown that faster eating rates support increased energy intake in adults and a meta-analysis of 22 ad libitum feeding trials demonstrated that adults who eat at a faster rate consume more energy [3]. Similar findings have been reported in studies conducted with children [4][5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 77%
“…While the type and quantity of foods consumed and the associated meal patterns that support sustained positive energy balance are important contributors to early weight gain, limited research has focussed on exploring whether children exhibit patterns of food oral processing, or "eating microstructure" patterns [2], that support increased energy intake within a meal. Previous research has shown that faster eating rates support increased energy intake in adults and a meta-analysis of 22 ad libitum feeding trials demonstrated that adults who eat at a faster rate consume more energy [3]. Similar findings have been reported in studies conducted with children [4][5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 77%
“…127 Intakes throughout the rest of the day also were not different between eating speed conditions. Given that high heterogeneity between studies has been reported 126 and that no studies have assessed long-term Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on this topic has reported a small to medium effect of eating rate on energy intakes at a meal, with lower intakes when eating speed is slow. 126 The difference in energy intakes was proportional to the difference in eating speed. However, there was no effect of eating rate on hunger after the meal and no difference in hunger ratings between meals of fixed content eaten at different speeds.…”
Section: Discussionmentioning
confidence: 99%
“…Eating slowly was associated with lower energy intake and there was no significant relationship between eating speed and hunger at the end of the meal or up to 3.5 hours later [1] . Eating fast is positively associated with excess body weight [2] .…”
Section: Eating Speed and Obesitymentioning
confidence: 78%